Fatty Acids 2017
DOI: 10.5772/67488
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Fatty Acids Metabolism as Treatment Strategy of Autism

Abstract: Autism is a neurodevelopmental disorder clinically presented as abnormalities in social interaction and communication, repetitive behaviors, usually accompanied by various neurobehavioral disorders, such as learning disability, hyperactivity and anxiety. It is well known that more than 50% of human brain weight is composed of lipids with a remarkably high content of long-chain polyunsaturated fatty acids (LCPUFA). Adequate supply of different fatty acids and lipids is critically needed by developing brain to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Emerging evidence shows altered fatty acid metabolism and homeostasis in ASD [113]. Acetate is a marker of glial metabolism and a metabolic substrate of astrocytes during fatty acid synthesis [114,115].…”
Section: Imaging For Metabolic Changesmentioning
confidence: 99%
“…Emerging evidence shows altered fatty acid metabolism and homeostasis in ASD [113]. Acetate is a marker of glial metabolism and a metabolic substrate of astrocytes during fatty acid synthesis [114,115].…”
Section: Imaging For Metabolic Changesmentioning
confidence: 99%
“…In general, these results indicate that lipids may be related to the autistic regression phenomenon. Nowadays, researchers have demonstrated that fatty acid correction may serve as a treatment strategy for autism, especially for their core symptoms [19,30,31]. Therefore, it is speculated that correcting lipids may also improve regression in autism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, abnormal fatty acid metabolism and lipid mediators have been reported to be related to the etiological mechanism in autism, and amelioration of impaired lipid metabolism can be recognized as a treatment strategy of autism [19][20][21]. Furthermore, researchers have experimentally shown that lipogenic enzymes, such as fatty acid synthase (FASN) and acetyl-CoA carboxylase (ACC), are highly expressed in the rodent brain during the early neonatal period and decline thereafter [21,22].…”
Section: Introductionmentioning
confidence: 99%